Inter- and intramolecular interactions in triptycene-derived bisphosphite hydroformylation catalysts: structures, energies, and caveats for DFT-assisted ligand design - Schmidt, Sebastian; Abkai, Golnar; Rosendahl, Tobias; Rominger, Frank; Hofmann, Peter (Organometallics, 2013)
The hydroformylation catalyst (L)RhH(CO)2, with a triptycene-derived bisphosphite ligand, and its iridium analogue were studied in solution, in the solid state, and computationally (DFT) in order to determine their molecular structures and to understand the equilibria between isomers. The predicted intramolecular distance of the two biphenyl side groups of these ligands strongly depends upon the treatment of inter- and intramolecular noncovalent interactions. A balanced treatment of these “weak” interactions is a prerequisite for obtaining reasonable structures and consequently also for determining relative energies of the different P-coordination modes. Low-temperature NMR studies confirm the equilibrium between axial-equatorial and equatorial-equatorial isomers in solution and have been used to estimate their relative stability in the equilibrium.
Gesehen am 05.07.2021